Risk associated with anesthesia for noncardiac surgery in children with congenital heart disease. Issue 5 (2nd May 2019) - Taylor, Dan; Habre, Walid
Summary: Database analysis has indicated that perioperative cardiac arrest occurs with increased frequency in children with congenital heart disease. Several case series and large datasets from ACS NSQIP have identified subgroups at the highest risk. Consistently, patients with single ventricle physiology (especially prior to cavopulmonary anastomosis), severe/supra‐systemic pulmonary hypertension, complex lesions, and cardiomyopathy with significantly reduced ventricular function have been shown to be at increased risk for adverse events. Based on these results, algorithms for assessing risk have been proposed. How hospitals and health care systems apply these guidelines to provide safe care for these challenging patient groups requires the application of modern quality improvement techniques. Each institution should develop a system which reflects local expertise and resources.